HALAL INDUSTRY CONTRIBUTION TO ECONOMIC GROWTH TO ACHIEVE SDGS IN MAQASHID SYARIAH PERSPECTIVE - Naja, Chifni Darun (UIN Mataram, 2023)
This research aims to describe how the contribution of the halal industry is to economic growth to achieve sustainable development in the perspective of maqashid sharia. This study used descriptive qualitative method. The approach used in this study was the library research method taken from journals and books related to research. This study analyzes. The results of the study show that the halal industry can increase economic growth, the halal industry as a means to achieve SDGs goals in accordance with maqashid sharia. the goals of the SDGs are aligned with the goals of the Islamic economy or even broader than the goals of the SDGs. the halal industry will support the implementation of sustainability development goals (SDGs) while maintaining maqashid sharia.